A Systematic Review of the Proportion of Blindness in the Population 50 Years and Older from Total Population-Based Surveys of Blindness and Visual Impairment. (4th March 2022) - Mushumbusi, Edmund; Buchan, John; Mactaggart, Islay; Macleod, David; Foster, Allen
ABSTRACT: Purpose: Epidemiological data is essential for planning; however, all-age population-based surveys are resource intensive. Rapid Assessment of Cataract Surgical Services methodology was developed in India in 1995 and subsequently promoted by the World Health Organisation for use worldwide. The commonly used Rapid Assessment of Avoidable Blindness (RAAB) evolved from this in 2005, constraining surveys to populations aged 50 or more based on the report 'The Epidemiology of Blindness in Nepal' (SEVA, 1988), where 78.7% of blindness occurred in people aged 50+. The purpose of this study is to examine whether more recent total-population-based surveys continue to find a similar proportion of blindness in the population aged 50+. Methods: A systematic literature review identified all population-based surveys of blindness published 1996–2017. Data extraction was undertaken by two independent researchers and compared. Results: The proportions of blindness (presenting visual acuity (PVA) <3/60) and moderate/severe visual impairment (MSVI) (PVA <6/18–3/60) from total population-based surveys in people aged 50+ ranged from 90% (Mali, 1996) to 45.8% (South Korea, 2015); the mean proportions across all surveys were 73.1% (95% CI, 60.4–85.8%) for blindness, and 73.8% (95% CI, 54.8–92.8) for MSVI. No trend over time or association with GDP was identified. Conclusion: This systematic literature review supports the rationale for constraining surveys to the population aged 50+ as this will greatly reduce sample size but still include a high proportion of total cases of blindness; paucity of total population-based surveys highlights the ongoing need for RAAB in service planning internationally.